EU migrant workers living in the East of England pre and post Brexit, 2015-2022 - Barnard, Catherine (UK Data Service, 2024)
The UK's decision to leave the EU has necessitated a wholesale rethink of UK immigration policy with the ending of free movement of workers. The motivations for this work then were to examine the immigration/worker protection boundary from a number of perspectives, with particular emphasis on the legal dimension. While understanding the developing EU and domestic (macro) perspective our aims at a micro level were to understand the legal problems EU citizens in low paid work in the UK were facing and how they resolve those problems. These legal problems were at times exacerbated by Brexit, particularly with the advent of the new digital EUSS (EU Settlement Scheme)- our research followed this in real time and recorded issues. One of our key findings and covered by the book published as a result of the dataset here is that of Pragmatic Law and the role of everyday community advice in the wider legal advice eco-system. This is an element of legal advice which to date had been little researched. Another key outcome was the contribution to literature on both EU free movement and citizenship studies, particularly in the context of vulnerable EU citizens. Our aim was to chart the experience and perceptions of EU migrants in the UK before, during and after Brexit to enable us to analyse the experience of EU migrants in seeking access to the social welfare system in the UK, the issues they have with immigration law and employment law, specifically the relationship between race and nationality discrimination and the Brexit process. We will seek to collect robust empirical evidence to establish whether the fact of Brexit, together with the policy changes, media pronouncements and political rhetoric, have an impact on both the experience of, and perceptions surrounding, the experience of EU migrants.